2009
DOI: 10.1007/s10661-009-0768-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mineral particles in winter fog of Beijing analyzed by TEM and SEM

Abstract: Aerosol samples were collected during winter fog and nonfog episodes in Beijing. Transmission electron microscopy (TEM) and scanning electron microscopy (SEM) were applied to study morphologies, sizes, and compositions of aerosol particles. TEM observation indicates that most mineral particles collected in fog episode are scavenged in fog droplets. Number-size distributions of mineral particles collected in fog and nonfog episodes show two main peaks at the ranges of 0.1-0.3 and 1-2.5 microm, respectively. Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 33 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…PM 2.5 mass concentration on the foggy day (14 November) reached the elevated level of 143 μ g m −3 (Figure 3). The stable meteorological conditions during the fog episode led to the accumulation of anthropogenic pollutants in urban areas [ Li and Shao , 2010a]. In addition, following the conversion from clear day (18 November) to hazy day (19 November), daily PM 2.5 mass concentrations increased from 67 μ g m −3 to 138 μ g m −3 .…”
Section: Resultsmentioning
confidence: 99%
“…PM 2.5 mass concentration on the foggy day (14 November) reached the elevated level of 143 μ g m −3 (Figure 3). The stable meteorological conditions during the fog episode led to the accumulation of anthropogenic pollutants in urban areas [ Li and Shao , 2010a]. In addition, following the conversion from clear day (18 November) to hazy day (19 November), daily PM 2.5 mass concentrations increased from 67 μ g m −3 to 138 μ g m −3 .…”
Section: Resultsmentioning
confidence: 99%
“…This instrument has been used effectively to study the mixing state and elemental compositions of individual aerosol particles. 21 For some particles, selected-area electron diffraction (SAED) was also obtained to verify their crystal phases. Volatile and semivolatile particles, such as water, some organic compounds, and NH 4 NO 3 , could not be analyzed because they were lost in the vacuum chamber of the electron microscope.…”
Section: Sample Analysesmentioning
confidence: 99%
“… 35 Li et al also found that the formation of secondary regular particles like gypsum was promoted by high humidity. 36 From above, it could be speculated that the formation and growth of rod-like calcium sulfate crystals is influenced by humidity. Furthermore, Gustafsson et al found that the amount of water adsorbed on the mineral dust aerosols decreased with the increasing particle diameters.…”
Section: Introductionmentioning
confidence: 99%